Analysis of Variables that Influence Digital Entrepreneurship in the Western Region of Indonesia Using Panel Data Regression - Erina Herwindalita (Department of Statistics, Faculty of Mathematics and Natural Sciences, Universitas Islam Bandung, 2025)
Abstract. Technological developments and digitalization provide a new space to support various entrepreneurial and productivity activities. However, digital-based entrepreneurship in Indonesia is not yet running optimally, especially in the western region of Indonesia, which has great potential. Thus, this research aims to analyze the variables influencing digital entrepreneurship in western Indonesia in 2020-2024 using a panel data regression model. Among the three model estimation approaches, it was found that the fixed effect model with cross-sectional weight was the most effective. The analysis results show that digital entrepreneurship in the western region of Indonesia experiences growth every year. Household internet access and the high school/equivalent net enrollment rate (NER) have a significant positive effect on digital entrepreneurship and productivity scores in the western region of Indonesia in 2020 – 2024. Meanwhile, the construction cost index and the gender empowerment index have no significant effect on digital entrepreneurship and productivity scores in the western region of Indonesia in 2020 – 2024.